The Effectiveness of the Flipped Classroom Strategy in Developing Self-Learning Skills Among Learners in the City of Misurata - Ibtisam Suleiman Mohammed bin Salah, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The study aimed to identify the effectiveness of the flipped classroom strategy in developing self-learning skills among learners in the city of Misrata, in light of modern trends that support the integration of technology in education. The study adopted an experimental method based on a two-group equivalent design (experimental and control) to measure the effect of the independent variable on the dependent variable. The study population consisted of second-year secondary (arts stream) female students at Al-Ghiran Secondary School in Misrata. The sample included (40) students who were divided equally into two groups, with (20) students in each group. To achieve the study objectives, the researcher designed a guide for implementing the flipped classroom strategy and applied it to the third unit in the subject of psychology and sociology over a period of two weeks. In addition, a self-learning skills measurement tool was used, and data were analyzed using the SPSS program. the results showed statistically significant differences in favor of the experimental group across all dimensions of self-learning skills, indicating the effectiveness of the flipped classroom strategy in developing these skills. Accordingly, the study recommended the need to train teachers on the use of modern teaching strategies, develop interactive learning environments that support self-directed learning, and promote the application of experimental research across different educational stages to improve the efficiency of the educational process.
Keywords: Flipped classroom strategy; self-learning skills; secondary education